The uniplex third: Enabling Single-domain role transitions in multiplex relationships - Li, Jian Bai and Piezunka, Henning (Administrative Science Quarterly)
Actors in a multiplex relationship$1 (Bone crossing multiple domains$1 (Bcan struggle to transition into new roles in one domain without disrupting existing interactions and the role hierarchy in another. Via an inductive study of intergenerational leadership successions in seven Chinese family firms, we examine how actors can complete such a single-domain role transition. We find that a succession between the founder/father and the successor/son is successful when the mother (i.e., the founder$1 (Bs wife) is active in the family but not the firm, acting as a trustworthy third party to the founder and successor in the family while staying nonpartisan to their business disagreements. Limiting her involvement to the family allows the mother to help the founder and successor maintain their existing family roles and interactions while transitioning into new roles in the firm. A mother involved in both firm and family could not stay nonpartisan between the founder and successor, which compromised their trust in her and prevented her from legislating over their multiplex relationship and facilitating the succession. We conceptualize the position of the uniplex third: the network position an actor occupies when she or he is connected in only one domain to two actors who have a multiplex dyadic relationship. Our cases reveal that the uniplex third position grants an actor authority via establishing trustworthiness and nonpartisanship relative to a multiplex dyadic relationship. The uniplex third party can thus facilitate change in one domain and maintain stability in another. We also observe how the mother is inhibited from occupying the uniplex third position when her kin are involved in the firm$1 (Bs top management. If conflicts exist in the firm between the mother$1 (Bs nuclear family and her kin, we find the mother disengages from succession-aiding activities in both family and firm domains. - Reproduced s
Keywords: Multiplex relationships, Economic sociology, Social networks, Succession in family firms